PERSPEKTIF MAHASISWI STIQ RAKHA AMUNTAI TERHADAP PENGHAPUSAN SKRIPSI SEBAGAI TUGAS AKHIR - Husin, Husin (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2023)
Thesis is a term used in Indonesia to illustrate a scientific paper in the form of a written presentation of undergraduate research results that discusses a problem or phenomenon in a particular field of science using applicable principles. The new policy issued by the Minister of Education to eliminate theses has significant implications in the world of education. Deleting a thesis can be considered a controversial step and has a wide impact, both on students, educational institutions and society in general. So in this journal the researcher aims to find out the perspective of students at the Rakha Amuntai College of Al-Qur'an Sciences (STIQ) regarding the elimination of their thesis as their final assignment. This research uses a qualitative method with a narrative research type. According to STIQ student Rakha Amuntai, according to the results of research on the deletion of theses as a final assignment, the government's policy regarding the deletion of theses is because many students think that theses are only burdensome and create unreadable piles in the library.